Improving Academic Achievement on Congregational Prayer Through Demonstration Method in Junior High Students - Hermawan, Asep Farid; Sobandi, Oban (Jurnal Keprofesian Guru Keagamaan, 2024)
This study aims to improve student learning outcomes in Fiqh subjects through the application of the demonstration method, namely by demonstrating the process or situation being studied so that students get a more meaningful learning experience. This study uses a Classroom Action Research (PTK) approach with the subject of 37 students in grade VII B MTs Ibadurrohman, Rancaekek District, Bandung Regency and is carried out in two cycles that include the stages of planning, implementation, observation, and reflection. The hypothesis proposed is that the demonstration method can effectively improve student learning achievement, with a target of at least 70% of students achieving a score above KKM 70. However, this study found several obstacles, such as the limitations of teachers' skills in using the method, differences in students' academic abilities, and time constraints that are influenced by a large number of students. Through observation and data analysis, this research is expected to contribute to improving the quality of Fiqh learning and offer practical recommendations to overcome existing challenges.